Frequency of the Audiometric Notch Following Excessive Noise Exposure - RISTOVSKA, Lidija; JACHOVA, Zora; ATANASOVA, Nikica (Archives of Acoustics, 2015)
The aim of the study was to determine the configuration of pathologic audiograms in patients with excessive noise exposure, and to calculate the frequency of notches in the audiogram in patients with and without excessive noise exposure by avoiding the effect of age-related hearing loss. We have analyzed 514 audiograms of 257 patients aged between 20 to 50 years: 240 patients (mean age of 38.7 years) with excessive noise exposure and 17 patients (mean age of 41.2 years) with notches in the audiogram, but without a history of excessive noise exposure. For statistical data analysis we have used the Chi-square test and Fisher exact test with the level of significance p < 0.05. Pathologic audiograms were classified into five different types: Slope at 4000 Hz (0.8%), Slope at 2000 Hz (15.1%), Notch at 4000 Hz (67.4%), Notch at 2000 Hz (0.8%), Flat (8.9%), and 7% were out of this classification. A total of 190 (79.2%) patients with excessive noise exposure had a notch in the audiogram. Left ear notches were the most common. Among the patients with notched audiograms, 91.8% had a history of excessive noise exposure, either occupational or nonoccupational, and 8.2% did not report any excessive noise exposure.